Buyer power and supplier incentives - Roman Inderst; Christian Wey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This paper investigates how the formation of larger buyers affects a supplier's profits and, by doing so, his incentives to undertake non-contractible activities. We first identify two chan-nels of buyer power, which allows larger buyers to obtain discounts. We subsequently exam-ine the effects of buyer power on the supplier's incentives and on social welfare. Contrary to some informal claims in the policy debate on buyer power, we find that the exercise of buyer power - even though reducing supplier's profits- may often increase a supplier's incentive to undertake welfare enhancing activities. – – Dieser Aufsatz entwickelt einen Modellrahmen zur Analyse der Wirkungen von Käufermacht auf Zwischenproduktmärkten. Zunächst werden Bedingungen identifiziert, die gewährleisten, daß Käufer mit großem Nachfragevolumen von Herstellern günstigere Konditionen erhalten als relativ kleine Käufer und somit über ,,Käufermacht“ verfügen. So dann untersucht die Arbeit, ob die Existenz von Käufermacht zu einer Verringerung der Innovationsanreize auf Seiten der Herstellern führt. Es wird gezeigt, daß eine solche Vermutung im Allgemeinen unzutreffend ist und daß Käufermacht im Gegenteil häufig höhere Investitionsanstrengungen auf der Herstellerseite induziert.
Keywords: D43; L13; L40; 330; Buyer Power; Investments; Competition Policy